La regulación de la moneda electrónica Criptomoneda y el Derecho Constitucional ecuatoriano - Murillo Soriano, Jonathan André (2025)
Within the Ecuadorian territory there is a Hyperregulation, thus safeguarding the particular interests and rights of people, thus article 1 of the civil code establishes the definition of law, establishing that it is the declaration of the sovereign will that, expressed in its form prescribed by the Constitution, commands, prohibits or allows. In this way, a legal aphorism is born which consists of all those actions that are not prohibited by law, are understood to be permitted, implying that everything that is not duly classified by express law specifying that it is prohibited, is understood to be permitted.............